Social transformations of rural communities through ecotourism : a systematic review / Velan Kunjuraman and Rosazman Hussin - Kunjuraman, Velan (Faculty of Hotel Management and Tourism, Univrsiti Teknologi MARA, Selangor, 2017)
This review paper observes the gap in the tourism literature, specifically on issues regarding communities’ qualities of life through eco(tourism) activities in both developed and developing countries. Based on the previous literature, it was found that the term ‘social transformation’ is often overlooked in the literature and less focused by tourism researchers. The issue of social transformation in tourism development is crucial to be studied in order to understand the communities’ quality of life when engaging in tourism activities and how they manage impacts. In this paper, literature on community participation in tourism activities and the issue of tourism impacts towards communities’ qualities of life is also studied. The main contribution of this paper is the discussion on the issue of social transformations of local communities through tourism is scarce and proposes the need to study by having some successful case studies in both developed and developing countries.